White Finger Millet (KMR-340): A comparative study to determine the effect of processing and their characterisation. (16th April 2022) - Navyashree, N.; Singh Sengar, Animesh; Sunil, C.K.; Venkatachalapathy, N.
Highlights: First report on effect of processing (roasting and germination), and characterization of White finger millet (KMR-340). Nutritional, functional, thermal, pasting and rheological properties, X-ray diffraction, and FTIR studies were studied for white finger millet (native, roasted and germinated). Processing methods significantly increased some nutritional components, non-essential amino acids, functional properties and thermal properties. Reduction in essential amino acids was observed. XRD patterns revealed reduction in percentage crystallinity in processed flours. White finger millet could be beneficial to human health similar to regular finger millet. Abstract: The white finger millet (WFM) KMR-340 flour: native (untreated), roasted (120 °C, 5 min) and germinated (30 ± 3 °C, 48 hrs) were characterised (nutritional, functional, thermal, pasting and rheological properties, X-ray diffraction, and FTIR). Germination significantly increased the protein, fibre, calcium, magnesium and antioxidant activity (14.66%) whereas decreased total ash, carbohydrate and fat. However, roasting significantly increased the carbohydrate, ash, fat, fibre and protein content. Roasting and germination significantly increased the non-essential amino acid contents, whereas the essential amino acid contents were reduced upon pretreatments. Though, processing methods improved the functional properties of millet flours, the pasting properties of the roasted and germinated flours were significantly varied from native flour. Rheological measurements revealed that all flour samples showed shear thinning behaviour (n < 1). The XRD patterns revealed that the percentage crystallinity reduced in the processed flours.